Self-assembly of peptide amphiphiles by vapor pressure osmometry and dissipative particle dynamics. Issue 47 (24th July 2018) - Seki, Taiga; Arai, Noriyoshi; Suh, Donguk; Ozawa, Taku; Shimada, Tomoko; Yasuoka, Kenji; Hotta, Atsushi
Abstract : Vapor pressure osmometry measurements and molecular simulation were carried out to investigate the self-assembly behavior of peptide amphiphiles. The results revealed that the head–water interaction plays an important role for their microstructure. Abstract : Peptide amphiphiles are one of the most promising materials in the biomedical field, so much effort has been devoted to characterizing the mechanism of their self-assembly and thermosensitive gelation. In this work, vapor pressure osmometry measurements were carried out to parameterize the thermosensitivity of interactions between peptide amphiphiles in an aqueous solution. The osmometry measurement verified that the peptides became more hydrophobic as temperature increased, which was quantitatively described with the Flory–Huggins χ parameter. Thereafter, a coarse-grained molecular model was used to simulate peptide amphiphiles dissolved in an aqueous solution. The temperature sensitive coarse-grained parameter a HW, which is the repulsive force between the hydrophilic head of the peptide amphiphile and water was estimated from the aforementioned experimentally obtained χ . Furthermore, the effects of concentration and temperature on the self-assembly behavior of peptide amphiphiles were quantitatively studied by dissipative particle dynamics. The simulation results revealed that a HW plays an important role in self-assembly characteristics and in the resulting microstructure of the peptide amphiphiles, which coincides with previous experimental and computational findings. The methodology in quantitatively linking the coarse-grained parameter from experiment and theory provides a sensible foundation for bridging future simulation studies with experimental work on macromolecules.